Crown angulation and inclination of Northern Thais with good occlusion - Jotikasthira D. (2014)
When patients of differing ethnicities are treated with one bracket system, negative consequences for the occlusion can result. This study investigated the crown angulation and inclination on study casts of 60 Northern Thais (30 males and 30 females) with a good occlusion. In all study casts, each tooth (except the third molars) was evaluated with the orthodontic Torque Angulation Device (TAD) twice on the right side; this was also performed twice on the left side. The mean of the two evaluations was used for the statistical analysis. The means of the males and females were compared with the independent Student t test. The results were that the crown angulation of the mandibular first and second molars was significantly higher in females (P<.01) and that the crown inclination of all teeth did not differ between the two sexes.